Chilocoris nitidus Mayr, 1865, the first Oriental burrower bug recorded in Tajikistan, with remarks on the zoogeography of the nitidus-group of Chilocoris Mayr, and an annotated checklist of Tajik Cydnidae (Hemiptera: Heteroptera) - Kłys, Grzegorz; Lis, Jerzy A. (Zootaxa, 2013)
The genus Chilocoris Mayr, 1865 (Cydnidae: Cydninae: Cydnini) comprises 85 species distributed in the Palearctic, Afrotropical, Oriental, and Australian Regions, with a single species reported from North America (Lis 1994, 1999, 2001, 2006a, 2006b; Imura 2011).